2017
DOI: 10.1175/jhm-d-15-0176.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of the June 2013 Flood-Producing Extreme Rainstorm over Southern Alberta

Abstract: A devastating, flood-producing rainstorm occurred over southern Alberta, Canada, from 19 to 22 June 2013. The long-lived, heavy rainfall event was a result of complex interplays between topographic, synoptic, and convective processes that rendered an accurate simulation of this event a challenging task. In this study, the Weather Research and Forecasting (WRF) Model was used to simulate this event and was validated against several observation datasets. Both the timing and location of the model precipitation ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 65 publications
(65 reference statements)
1
35
0
Order By: Relevance
“…From June 19 to 22, 2013, heavy rainfall and snowfall (at high elevations) with local amounts exceeding 300 mm fell over a broad region of the Canadian Rocky Mountains of southeastern British Columbia and southwestern Alberta, and the foothills and adjacent plains of southern Alberta, Canada (Milrad et al, 2015;Liu et al, 2016;Kochtubajda et al, 2016;. This heavy precipitation resulted from moisture convergence from the Pacific and from the Canadian Prairies and 5 US Great Plains through evapotranspiration (Milrad et al, 2015;Li et al, 2017). At high elevations, rain and then snow fell on a deeper than normal, late-lying snowpack leading to rain-on-snowmelt which enhanced runoff generation (Fang and Pomeroy 2016;Pomeroy et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…From June 19 to 22, 2013, heavy rainfall and snowfall (at high elevations) with local amounts exceeding 300 mm fell over a broad region of the Canadian Rocky Mountains of southeastern British Columbia and southwestern Alberta, and the foothills and adjacent plains of southern Alberta, Canada (Milrad et al, 2015;Liu et al, 2016;Kochtubajda et al, 2016;. This heavy precipitation resulted from moisture convergence from the Pacific and from the Canadian Prairies and 5 US Great Plains through evapotranspiration (Milrad et al, 2015;Li et al, 2017). At high elevations, rain and then snow fell on a deeper than normal, late-lying snowpack leading to rain-on-snowmelt which enhanced runoff generation (Fang and Pomeroy 2016;Pomeroy et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…This extreme weather event has been investigated in details in the last few years from the perspectives of atmospheric and climate modelling. Li et al (2017) showed that the Weather Research and Forecast (WRF) atmospheric model at convectionpermitting resolution (3-km) demonstrated reasonable skill in simulating the spatial and temporal evolution of precipitation 15 patterns before and during the flood. They investigated with the model the dynamical features that led to the generation of heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(). Simulation of this event (Li et al ., ) illustrated the evolution of precipitation during the convective phase.…”
Section: Introductionmentioning
confidence: 99%